Human innate lymphoid cell activation by adenoviruses is modified by host defense proteins and neutralizing antibodies - Paris, Océane; Mennechet, Franck J. D.; Kremer, E. J. (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs), the complements of diverse CD4 T helper cells, help maintain tissue homeostasis by providing a link between innate and adaptive immune responses. While pioneering studies over the last decade have advanced our understanding how ILCs influence adaptive immune responses to pathogens, far less is known about whether the adaptive immune response feeds back into an ILC response. In this study, we isolated ILCs from blood of healthy donors, fine-tuned culture conditions, and then directly challenged them with human adenoviruses (HAdVs), with HAdVs and host defence proteins (HDPs) or neutralizing antibodies (NAbs), to mimic interactions in a host with pre-existing immunity. Additionally, we developed an ex vivo approach to identify how bystander ILCs respond to the uptake of HAdVs ± neutralizing antibodies by monocyte-derived dendritic cells. We show that ILCs take up HAdVs, which induces phenotypic maturation and cytokine secretion. Moreover, NAbs and HDPs complexes modified the cytokine profile generated by ILCs, consistent with a feedback loop for host antiviral responses and potential to impact adenovirus-based vaccine efficacy.